Role of Yoga in Augmentation of Problem-Solving Ability among selected University Players. - Vijay Laxmi (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
The aim of the present study was to find out the Role of Yoga in augmentation of problem-solving ability among selected University Players i.e., Chaudhary Devi Lal University (CDLU) and Maharishi Dayanand University (MDU). Fifty (N-50) University level male and female yoga players were selected as subjects and they were further divided into two groups as per the University they played for namely Chaudhary Devi Lal University (CDLU) and Maharishi Dayanand University (MDU). Each group comprised 25 players each. The single group pre and post design was used for data collection. Problem Solving Ability of the players was measured by using Problem Solving Ability Test (PSAT- d) developed by L.N. Dubey. Problem Solving Ability of players were measured before and after 4 weeks. The result of the study revealed that there is a significant difference found between pre and post yoga camp in university players (p=0.001) on Problem Solving Ability of all selected University players.